Greenland, landscape of Goodenough Land, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
"Looking west into Goodenough Land from the ice-free valley between Kjerulf Fiord and Hisinger Glacier. Aug. 2, 1931. From: The Fiord Region of East Greenland, Fig. 177."; Caption from Boyd, L. A., (1935). The Fiord Region of East Greenland (pp.125). New York: American Geographical Society. "Fig. 177 - Looking west into Goodenough Land from the ice-free valley between Kjerulf Fiord and Hisinger Glacier. (For detailed map see geogr. Rev., Oct., 1932, Pl. III.) Aug. 2, 1931 (XII)."